Low Isozyme Variation in Native and Transplanted Populations of the Endemic Philippine Silver Perch, Leiopotherapon plumbeus (Kner, 1864) from Three Lakes in the Philippines - Quilang, Jonas P.; Basiao, Zubaida U.; Pagulayan, Roberto C.; Roderos, Remedios R.; Cao, Ernelea P. (2008)
The silver perch,Leiopotherapon plumbeus (Kner, 1864), is an endemic and economically important fish in the Philippines. A native species of Laguna de Bay, the silver perch was transplanted from this lake to Sampaloc Lake in the late 1950s and Taal Lake in the early 1970s. Morphological variation has been observed among the native and transplanted populations of the silver perch. In this study, genetic variation within and between the native and transplanted populations was examined using isozyme electrophoresis. Four sites were sampled: two in Laguna de Bay (Binangonan and Tanay) and one each in Sampaloc Lake and Taal Lake. Twenty-two (22) loci were scored but only one locus (PGM*) was polymorphic by the 95% criterion and only two loci (ADH* and PGM*) were polymorphic by the 99% criterion. The average heterozygosities, genetic distances and FST values of specimens from the four sites were very low, suggesting that the native and transplanted populations had very low genetic variation and that they were genetically homogeneous despite the presence of morphological variation. The low genetic variation could possibly be due to a population bottleneck in the native population in Laguna de Bay in the past and to the low genetic variation of the founders in the transplanted populations.
Keywords: Fish declines; Endemic animals